1981
DOI: 10.1128/jcm.14.3.352-354.1981
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis and Compartmentalization of the Cerebral Ventricles Caused by Enterobacter sakazakii

Abstract: A necrotizing meningoencephalitis complicated by ventricular compartmentalization and abscess formation caused by Enterobacter sakazakii in a previously healthy 5-week-old female is described. A detailed description of the isolate is presented. This communication firmly establishes the pathogenicity of E. sakazakii. We are grateful to M. A. Asbury of the Enteric Section, Centers for Disease Control, for confirming the identification of the isolate, to John J. Farmer III of the Centers for Disease Control and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…Newborns with meningitis due to E. sakazakii have a poor prognosis. The fatality rate in the present study was 80%; previous studies have reported 40% (1,7,8,20).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Newborns with meningitis due to E. sakazakii have a poor prognosis. The fatality rate in the present study was 80%; previous studies have reported 40% (1,7,8,20).…”
Section: Discussioncontrasting
confidence: 63%
“…Enterobacter sakazakii was described in 1980 as a new member of the Enterobacteriaceae (3) and has been reported as a cause of neonatal meningitis (1,3,7,8,11,20). The natural habitat of E. sakazakii is unknown, but it has been isolated from a number of hospital sources (3).…”
mentioning
confidence: 99%
“…Eight samples were found to contain Escherichia coli by both methods; one sample showed fluorescence in the LSB-MUG tube, but it was unable to be confirmed as Escherichia coli due to the presence of another enteric bacterium, Enterobacter sakazakii. This organism is basically a yellow-pigmented Enterobacter cloacae (10,13), and like olher Enterobacter species, it is capable of producing a viscous, slimy capsular material on EMB agar which can mask other organisms present in the sample (6). The natural reservoir of this organism is unknown, but it probably comes from the feces of humans and animals, sewage, water, or soil (15).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inefficient cleaning of the feeding bottle and utensils could result in the accumulation of the organism and act as a source of infection. Kleiman et al (1981) and Adamson & Rogers (1981) reported separate cases of previously healthy 5-week-old infants admitted to hospital with meningitis caused by E. sakazakii, showing that the infection can also be acquired in the home environment.…”
Section: Environmentmentioning
confidence: 99%